Nutrition and performance in masters athletes - Reaburn, Peter R.J. (Boca Raton CRC Press / Taylor & Francis Group, 2015)
"This book examines the aging process, its effect on sports performance, the methods to maximize sports performance, and the unique nutritional needs of masters athletes. More importantly, the book focuses on practical ways to minimize the age-related declines in performance and health by examining ways to maximize speed, endurance, and strength development in order to slow the inevitable age-related performance decline. The insights discussed in the text enable readers to both improve performance and better understand their bodies' responses to exercise as they age, through correct training methodology and nutritional practices."-- Provided by publisher.
Physiological changes affecting the nutritional needs of masters athletes / David Jenkins, Tina Skinner and Kate Bolam -- Physiological changes affecting performance of masters athletes / Benjamin J. Dascombe, Nathan Elsworthy, Brendan Scott, Dean V. Sculley and Peter R.J. Reaburn -- Energy needs of masters athletes / Nuala M. Byrne and Andrew P. Hills -- Carbohydrate needs of masters athletes / Gregory R. Cox -- Fat needs in masters athletes / Nathan A. Johnson and Stephen R. Stannard -- Protein needs of masters athletes / Mark A. Tarnopolsky -- Vitamin needs of masters athletes / Jeanick Brisswalter -- Mineral needs of masters athletes / Erica Hirsch, Mrinalini Sharma and Stella Lucia Volpe -- Fluid, electrolytes and hydration needs of masters athletes / Kathryn Jackson -- Supplement use in masters athletes / Ben Desbrow, Greg Shaw and Gary Slater -- Ergogenic aids for masters athletes / Vincent J. Dalbo, Michael D. Roberts and Aaron T. Scanlan -- Nutrients, health and chronic disease in masters athletes / Janelle A. Gifford, Helen T. O'Connor, Alexandra L. Honey and Ian D. Caterson -- Drug and nutrient interactions in masters athletes / Kathleen M. Knights and Arduino A. Mangoni -- Training and nutrition needs of the masters endurance athlete / Michael Leveritt and Juliet Wiseman -- Training and nutritional needs of the masters ultra-endurance athlete / Paul B. Laursen -- Training and nutritional needs of the masters sprint athlete / Marko T. Korhonen, Marko Haverinen and Hans Degens -- Training and nutrition needs of the masters strength/ power athlete / Michael D. Roberts, Vincent J. Dalbo and Thomas W. Buford -- Training and nutritional needs of the masters team sport athlete / Aaron J. Coutts, Amy E. Mendham and Rob Duffield
Includes bibliographical references and index.
Keywords: Athletes -- Nutrition; Sports for older people -- Physiological aspects